International Aid and China's Environment - Morton, Katherine (Routledge Studies on China in Transition, 2005)
Rapid economic growth in the world's most populous nation is leading to widespread soil erosion, desertification, deforestation and the depletion of vital natural resources. The scale and severity of environmental problems in China now threaten the economic and social foundations of its modernization. Using case studies, Morton analyzes the relationship between international and local responses to environmental problems in China, challenging the prevailing wisdom that weak compliance is the only constraint upon local environmental management in China. It advances two interrelated discussions: first, it constructs a conceptual framework for understanding the key dimensions of environmental capacity. This is broadly defined to encompass the financial, institutional, technological and social aspects of environmental management. Second, the book presents the results of an empirical inquiry into the implementation of donor-funded environmental projects in both China's poorer and relatively developed regions. By drawing upon extensive fieldwork, it seeks to explain how, and under what conditions, international donors can strengthen China's environmental capacity, especially at the local level. It will be of interest to those studying Chinese politics, environmental studies and international relations.